An automated and robust method for modelling X-ray beamlines with plane grating monochromators - Patrick Yuheng Wang; Murilo Bazan da Silva; Georg Held; Hongchang Wang; Kawal Sawhney; Andrew C. Walters (Journal of Synchrotron Radiation)
The plane grating monochromator (PGM) is an optical instrument used in the majority of soft X-ray beamlines. Despite its ubiquity, the PGM efficiency can easily be overestimated, because the geometry of many modern PGMs can lead to unexpected blocking of the beam. We have developed a new workflow in Python for simulating PGMs, thus extending the capabilities of SHADOW3, a well established ray tracing software tool. We have used our method to simulate the flux on branch C of the Versatile Soft X-ray (VerSoX) beamline B07 at Diamond Light Source. The simulation results demonstrate qualitative agreement with the experimental measurements, confirming the robustness of the proposed methodology.